Rule of Law and Right to Democracy in International Law: To Contradict or Conform to Constitutionalism? - Thamilmaran, V.T. (University of Colombo, 2011)
Rule of Law, a principle in constitutional law and a concept in political science discourse has been understood for more than a century as a heavily loaded tenet of democracy. Governments were to be tested for their qualitative character of democracy by employing the yardstick of rule of law. Constitutionalism has come into being as one of the best means of ensuring rule of law. By asserting the supremacy of the constitution the principle of rule of law was to be embodied into various constitutions around the world. +RZHYHU GXULQJ WKH FROG ZDU SHULRG WKH 6RFLDOLVW EORFN PDLQWDLQHG WKDW µSHRSOH GHPRFUDF\¶VKRXOGSUHYDLORYHUWKHµZHVWHUQOLEHUDOGHPRFUDF\¶DQGKHQFHWKHTXDOLW\RI thHUXOHRIODZFRXOGEHWHVWHGRQO\IRULWVDELOLW\WRVDIHJXDUGLQJSHRSOHV¶UXOH $VVXFK Constitutionalism for such States was nothing but the supremacy of the constitution that entrenched the peoples rule. Sovereignty of the people was thus explained not in the sense of ownership but in its characteristic of being possessed by the rulers. With the collapse of the Soviet Union and other socialist regimes, debates over constitutionalism resurfaced with a new vigour in that international human rights regime 175 has come to influence and dominate domestic laws in many of those newly admitted members to the democratic guild. Since early 1990s, there has been a debate among scholars of international law as to the legality of the right to democracy in international law. In light of the globalization process of the last two decades, many States have to face the challenge of either rewriting their constitutions or allowing international human rights norms to roll back into their domestic legislative sphere. There were occasions of forceful introduction of these norms into domestic law and r legality of that has not been checked in any international forum. As such, this paper attempts to discuss the legal basis of the claim of right to democracy from constitutional and international law perspective. Analysis of the constitutional principle of rule of law and its scope and application would form the main basis for testing the legality of the claim over democracy